THE EFFECT OF FUNDAMENTAL FACTORS ON TRIPLE BOTTOM LINE AND FIRM VALUE - Nana Arviana; Masodah Wibisono (JRAK, 2023)
Every company must set aside a portion of the profits because it has some responsibilities towards the environment and society. This research aims at finding clear evidence of the fundamental effect of the triple bottom line in mediating profitability, liquidity, and leverage on a company’s values. Manufacturing companies listed on the Indonesia Stock Exchange are the object of this research. The data were analyzed using path analysis with SPSS version 25 software. This finding showed that profitability, leverage, and liquidity did not affect the triple bottom line. On the other hand, profitability did affect the value of the company, while liquidity, leverage, and triple bottom line did not.